Degradability and biofouling of oxo-biodegradable polyethylene in the planktonic and benthic zones of the Arabian Gulf. (January 2020) - Abed, Raeid M.M.; Muthukrishnan, Thirumahal; Al Khaburi, Maryam; Al-Senafi, Fahad; Munam, Abdul; Mahmoud, Huda
Abstract: Little is known about the degradability of oxo-biodegradable polyethylene (OXO-PE) and its surface fouling bacterial communities in the marine environment. The degradation of OXO-PE, PE and polyethylene terephthalate (PET) was compared at two depths (2 m and 6 m) in the Arabian Gulf. Scanning electron microcopy (SEM) revealed more fissure formation on OXO-PE and PE than on PET, indicating physical degradation. The formation of hydroxyl groups and carbonyl bonds, by Fourier-transform infrared spectroscopy (FTIR), suggests chemical degradation of OXO-PE. Plastisphere bacterial communities on OXO-PE and PE were different than on PET. Proteobacteria, Bacteriodetes and Planctomycetes were detected on all plastics, however, sequences of Alteromonas and Zoogloea were OXO-PE-specific suggesting a possible involvement of these bacterial genera in OXO-PE degradation. We conclude that OXO-PE shows increased signs of degradation with time owing to the combination of abiotic and biotic processes, and its degradation is higher in the benthic than in the planktonic zone. Highlights: Oxo-biodegradable polyethylene (OXO-PE) showed increased signs of physical and chemical degradation over time than PE and polyethylene terephthalate (PET). Higher degradability of OXO-PE was detected in the benthic (6m) than the planktonic (2m) zones of exposure of the Arabian Gulf. The abundance and composition of the plastisphere bacterial communities were influenced by plastic type, duration and depth of exposure. The detection of OXO-PE-specific bacterial genera Alteromonas and Zoogloea suggests their possible involvement in mediating biotic degradation.